2015
DOI: 10.1021/acsami.5b04351
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Isolation of cis-2 Regiospecific Ethylene-Tethered Indene Dimer–[70]Fullerene Adduct for Polymer Solar Cell Applications

Abstract: Although the utilization of [70]fullerene bis-adducts can enhance the power conversion efficiencies of polymer solar cells (PSCs) owing to their strong absorption intensities and high-lying lowest unoccupied molecular orbital energy levels, this synthetic strategy typically yields a mixture of regioisomers that would mask the intrinsic device performances depending on the substituent pattern on the [70]fullerene derivatives. In this study, a single cis-2 regioisomer of C70 bis-adduct (cis-2-[70]BIEC) has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…1b), 40 in which two indene units were attached at a-bonds of hexagons next to each other. 38 Note here that steric hindrance between the addends would inhibit the formation of such a close substitution pattern if the tether-directed effect was absent. 23,27 The OPV based on BIE- [70]fullerene bis-adduct isomer with cis-2 conguration, cis-2- [70]BIEC and poly(3-hexylthiophene) showed a remarkable PCE of 4.2%, which was higher than those with the regioisomer mixture of BIE- [70]fullerene bis-adduct (2.2%), BIE- [70] fullerene mono-adduct (2.2%), BIE-[60]fullerene bis-adduct isomer with cis-2 conguration (2.8%), and even [70]PCBM (3.8%).…”
Section: -35mentioning
confidence: 99%
“…1b), 40 in which two indene units were attached at a-bonds of hexagons next to each other. 38 Note here that steric hindrance between the addends would inhibit the formation of such a close substitution pattern if the tether-directed effect was absent. 23,27 The OPV based on BIE- [70]fullerene bis-adduct isomer with cis-2 conguration, cis-2- [70]BIEC and poly(3-hexylthiophene) showed a remarkable PCE of 4.2%, which was higher than those with the regioisomer mixture of BIE- [70]fullerene bis-adduct (2.2%), BIE- [70] fullerene mono-adduct (2.2%), BIE-[60]fullerene bis-adduct isomer with cis-2 conguration (2.8%), and even [70]PCBM (3.8%).…”
Section: -35mentioning
confidence: 99%
“…[32][33][34][35][36][37][38] PCEs up to 10.6% have been achieved using isomeric mixtures of fullerene bis-adducts, such as indene-C 61 -bis-adducts (IC 61 BA) in a solution processed tandem solar cell. [33] Although not all isomerically pure bis-regioisomers have been tested in solar cell devices, most of the reported cases have demonstrated that pure regioisomers many times perform better than the corresponding isomeric mixtures, [39][40][41][42][43] although some exceptions have also been noted. [21,41,44] These observations justify the necessity to synthesize pure bis-adducts, and this in turn has led to a renaissance of the methods and reagents available to decrease the number of fullerene multiadduct derivative isomers.…”
Section: Regioisomers Observedmentioning
confidence: 99%
“…Recent activity in this area has resulted in new and regioisomerically pure bis-adducts that have performed reasonably well in OPV devices. [37,40,42] In some cases, even when using the tether-directed method, the number of isomers obtained is still rather large, for example, in the case of the synthesis of tethered bis-PC 61 BM (phenyl butyric acid methyl ester-C 61 ) [45] and tethered bis-DPM-C 60 (diphenyl methano) [44] for which the number of isomers obtained was 7 and 12, respectively. The main reasons for these observations are the lack of symmetry of the addend, in which case diastereomers can also be observed and Figure 2.…”
Section: Regioisomers Observedmentioning
confidence: 99%
See 2 more Smart Citations